News in Cancer-Related Pain Management - Cornelia NITIPIR; Andreea PAROSANU; Lucian ALECU; Ana Maria POPA; Cristian IACIU; Mihaela OLARU; Adrian TULIN; Iulian SLAVU; Valentin CALU; Cristina ORLOV-SLAVU (Modern Medicine)
Introduction: Cancer related- pain causes a negative psychosocial and physical impact on patients’ lives. The purpose of this review was to investigate the current strategies for cancer pain treatment. Material and Methods: We conducted a PubMed search of the literature published from 2018 to 2020, and details were extracted from the articles with adequate study quality. Discussion: Of 63 titles, 19 studies were selected and used in review. Conclusions: This review article focuses on the novel treatments available for cancer pain management.